2019
DOI: 10.1136/bmjopen-2018-028170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, nature and risk factors for medication administration omissions in English NHS hospital inpatients: a retrospective multicentre study using Medication Safety Thermometer data

Abstract: ObjectiveTo determine the prevalence, nature and predictors of patients having medication administration omissions in hospitals.MethodsAll medication administration omissions data collected using the standardised methodology of the Medication Safety Thermometer in January 2015 were examined. Hospital inpatients prescribed at least one medication were included in the analysis. Multilevel logistic regression models ascertained the effects of patients’ gender, age, number of prescribed medicines, ward specialty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
3
11
0
2
Order By: Relevance
“…'Preventable' dose omissions have emerged as an important target for remedial intervention in this research. The ratio of 'preventable' to 'non-preventable' omissions that we observed appears broadly similar to data from general hospital studies [23,24,27]. Available evidence for the causes of unavailable drug related 'preventable' omitted doses from mental health hospitals [14][15][16] identifies causative factors such as medicines logistics, but detail is often limited to codes on prescription charts or brief descriptions in incident reports.…”
Section: Implications Of Findingssupporting
confidence: 72%
See 1 more Smart Citation
“…'Preventable' dose omissions have emerged as an important target for remedial intervention in this research. The ratio of 'preventable' to 'non-preventable' omissions that we observed appears broadly similar to data from general hospital studies [23,24,27]. Available evidence for the causes of unavailable drug related 'preventable' omitted doses from mental health hospitals [14][15][16] identifies causative factors such as medicines logistics, but detail is often limited to codes on prescription charts or brief descriptions in incident reports.…”
Section: Implications Of Findingssupporting
confidence: 72%
“…medications involved and underlying reasons especially unavailable drugs or 'blank boxes' not signed for administration which may be preventable) or predicting factors [13,21]. More in-depth investigations focusing on omitted doses have helped address these needs in general hospitals including highlighting the a significant proportion of potentially 'preventable' omissions [22][23][24], but this data may not be generalizable to mental health hospitals and the evidence base in psychiatry is largely absent except for two single site UK studies restricted to reported missing signatures for medicines administration [25] and overall omitted dose rates within elderly care [26]. This highlights a need for further research across multiple mental health hospitals that explores in detail the type, preventability Funding: The author(s) received no specific funding for this work.…”
Section: Introductionmentioning
confidence: 99%
“…The body of knowledge has established that 10% of patients are harmed by healthcare, the primary cause of which seem to be associated with adverse effects of medication (de Vries et al, 2008;Cottney, 2015;Rostami et al, 2019). Many studies have reported that these preventable drug adverse effects are caused by medication errors, the administration medication errors being the most common (Elliott et al, 2018;Rostami et al, 2019). In this study, it was found that the frequency of WTMAEs was 47.8% of which early and late time medication administration errors accounted for 47.2 and 4.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…O NHS criou, em 2010, como parte de um programa de melhoria da qualidade, a ferramenta NHS Safety Thermometer, que tem por objetivo fornecer a prevalência instantânea dos EA, através da mensuração de danos no foco do cuidado ao paciente 10 . Trata-se de um programa que inclui um conjunto de ferramentas de mensuração de prevalência de EA, chamadas de Classic Safety Thermometer, Mental Health Safety Thermometer, Maternity Safety Thermometer e Children & Young People Safety Thermometer, relacionadas individualmente aos mais diversos objetivos, como quedas, lesão por pressão, tromboembolismo venoso, infecção o trato urinário, maternidade, saúde mental, crianças e idosos e medicamentos 7,10,15,[21][22][23][24] .…”
Section: Medication Safety Thermometerunclassified
“…Rostami et al 21 determinaram a prevalência, natureza e fatores de omissão de medicamentos em pacientes através da compilação dos dados coletados em 37 hospitais que utilizaram o MedST, em janeiro de 2015. A prevalência de omissão de medicamentos encontrada na amostra foi de 30% e a recusa pelo paciente foi a causa de 50% das omissões.…”
Section: Medication Safety Thermometerunclassified